EXPLORING FORMAL MENTORING PROGRAMMES WITHIN THE PRACTICUM PROGRAMMES IN KAZAKHSTAN - Turmukhambetova, Lyazat (Graduate School of Education, 2022)
Initial teacher education (ITE) is attributed a special role, as it prepares teacher candidates to meet the constantly evolving teaching standards tailored in accordance with the national contexts (Bridges et al., 2014; Kosnik et al., 2016, Murray et al., 2019). The educational reform has also impacted Kazakhstan, changing the discourse of teacher professionalism in the country (Fimyar, 2014). Therefore, it is critical that teacher education programmes could successfully integrate the teaching profession's practical and theoretical underpinnings to successfully promote the educational reform, making the practicum programme the leading facilitator of practice-based learning within ITE. The mentoring role can be essential in delivering and helping student teachers integrate their theoretical knowledge into practice and developing their situated understanding (Winch et al., 2015) of the teaching profession through reflection and collaboration. This multiple- case study aimed to explore how the formal mentoring programmes are practised and conceptualised in two Kazakhstani school-university partnerships. By conducting 23 one-on-one semi-structured interviews, one paired interview, four focus groups and documentation analysis, this study revealed multiple understandings of mentoring, including the elements of traditional and transitional mentoring approaches. This study provides an evidence-based representation of the conceptual mentoring model by Ambrosetti, Knight, and Dekkers’ (2014) on maximising the mentoring potential for ITE students by modifying it through the additional lens of the practicum advisors and positioning the conceptual understanding of mentoring within the framework. As the study demonstrated, the perceptions of mentoring by the main stakeholders within the school- university partnership may shape the mentoring practices, inevitably affecting all mentoring stages and the relational and developmental outcomes.
Keywords: Type of access: Restricted; mentoring; initial teacher education; practicum programme